2018
DOI: 10.1016/j.ijpe.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Managing demand uncertainty: Probabilistic selling versus inventory substitution

Abstract: Portal del coneixement obert de la UPC http://upcommons.upc.edu/e-prints Aquesta és una còpia de la versió author's final draft d'un article publicat a la revista International journal of production economics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Those problems are consumer demand, perception, and buying behavior, as well as daily demand prediction and inventory management. Consumer demand, perception, and buying behavior can be approached with a probabilistic system [ 140 , 141 , 142 ], for instance, uncertainty concerning what food products are expected to be bought. Meanwhile, daily demand prediction and inventory management can be addressed with an optimization paradigm [ 143 , 144 ].…”
Section: A Taxonomy Of Ci-based Problems In the Food Supply Chainmentioning
confidence: 99%
“…Those problems are consumer demand, perception, and buying behavior, as well as daily demand prediction and inventory management. Consumer demand, perception, and buying behavior can be approached with a probabilistic system [ 140 , 141 , 142 ], for instance, uncertainty concerning what food products are expected to be bought. Meanwhile, daily demand prediction and inventory management can be addressed with an optimization paradigm [ 143 , 144 ].…”
Section: A Taxonomy Of Ci-based Problems In the Food Supply Chainmentioning
confidence: 99%
“…In this vein, Dolgui et al (2013) reported that safety lead times may have a greater impact on firm performance than safety stock, especially for multi-level inventory systems, thereby contributing to firm responsiveness to market demand. Indeed, many factors may influence probabilistic demands, such as the nature of the product, the number of manufacturing system stages (single stage or multiple stages) and serving an unlimited number of customers (Zhang et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To establish the optimal quantities of inventory of a product, the demand must be considered over a period of time (days, weeks, months, and years), however, when we obtain this information, the product can have a constant or variable demand; which would hinder the process of setting the optimal quantities need to order. In any case, the responsible of these decisions aims to create and implement techniques, methods and methodologies that allow good inventory management to accurately determine the quantities to be ordered at the right time [5][6][7].…”
Section: Introductionmentioning
confidence: 99%